Recent advances in ultrasensitive electrochemical sensors and biosensors for determination of antibiotics in environment samples - Zheng, Alvin Lim Teik; Teo, Ellie Yi Lih; Yiu, Pang Hung; Boonyuen, Supakorn; Chung, Eric Lim Teik; Andou, Yoshito (Springer Science, 2024)
Antibiotics have undeniably served as a crucial factor in protecting both human and animal populations from infections caused by bacteria. Electrochemical sensing has become a promising and developing alternative for measuring antibiotic residuals in various matrices such as environment and food. It is crucial to give priority to the advancement of technologies that have enhanced sensitivity and selectivity. Electrochemical sensors provide a more efficient and accurate method for detecting the presence of antibiotic compounds, as opposed to traditional laboratory detection procedures. This review seeks to offer an in-depth overview of the recent progress achieved in the past five years in detecting different antibiotics using a range of electrochemical sensors. These sensors include those based on MXene, MOF, graphene, and polymers. The fabrication and utilization of these sensors not only represent a substantial advancement in detection capacities but also create opportunities for tackling the challenges presented by antibiotic residues in the environment. This review also explores into the challenges, opportunities, and prospects associated with the aforementioned electrochemical sensors, offering a holistic perspective on their role in mitigating the environmental impacts of synthetic antibiotics.